The Effect of Employee Engagement, Organizational Commitment, and Work Motivation on Organizational Citizenship Behavior - Michael Bryan Putra Cristian; Audita Nuvriasari (Arthatama: Journal of Business Management and Accounting, 2025)
Organizational Citizenship Behavior (OCB) plays a vital role in enhancing organizational effectiveness, particularly in work environments that demand high collaboration and responsibility, making it important to understand the factors that encourage employees to engage in extra-role behaviors. This study aims to examine the effect of employee engagement, organizational commitment, and work motivation on OCB. Using a quantitative approach, data were collected through a structured questionnaire and analyzed using regression analysis to determine the influence of each independent variable. The findings indicate that employee engagement and work motivation have a positive and significant effect on OCB, showing that employees who feel psychologically involved in their work and are highly motivated tend to display stronger voluntary behaviors that support organizational goals. In contrast, organizational commitment does not have a significant effect on OCB, as the dominant form of commitment is continuance-based, which encourages employees to focus on formal job requirements rather than discretionary contributions. The study concludes that efforts to foster OCB should prioritize strengthening employee engagement and work motivation rather than relying solely on organizational commitment.